Comparison of hot deformation behaviour and microstructural evolution for Ti-5Al-5V-5Mo-3Cr alloys prepared by powder metallurgy and ingot metallurgy approaches. (5th May 2019) - Zhao, Qinyang; Yang, Fei; Torrens, Rob; Bolzoni, Leandro
Abstract: To realize the systematic comparison of the hot workability and guide the further hot-processing of powder metallurgy (PM) and ingot metallurgy (IM) Ti-5Al-5V-5Mo-3Cr (Ti-5553) alloys, the hot deformation behaviour and microstructural evolution of the two alloys were investigated at a wide temperature range of 700 °C–1100 °C and strain rate of 0.001 s −1 -10 s −1 . The activation energy maps and processing maps for both PM and IM alloys were constructed, as well as the specific deformation mechanisms were identified for each processing region. The results showed that PM alloy has lower deformation resistance, smaller activation energy and larger optimal processing windows than those of IM alloy. The dynamic α precipitation mechanisms in PM alloy were diffusional globularization and coarsening, rather than diffusionless shearing and fracturing in IM alloy. The extensive dynamic recrystallization (DRX) happened at 900 °C–1050 °C for PM alloy and at 1000 °C–1100 °C for IM alloy. The DRX process was dominated by discontinuous dynamic recrystallization (DDRX) for PM alloy while continuous dynamic recrystallization (CDRX) for IM alloy. Furthermore, PM alloy had smaller flow instability region than IM counterpart in the hot processing map. The schematic deformation mechanism maps were eventually developed for both PM and IM Ti-5553 alloys. Graphical abstract: Unlabelled Image Highlights: Ti-5553 alloy with better workability than ingot-casting (IM) counterpart was prepared by fast powder-consolidation (PM). Activation energy maps and processing maps of PM and IM alloys were constructed to evaluate their hot workability. Comprehensive comparison of deformation mechanisms of the alloys is achieved by the deformation mechanism maps. Different dynamic recrystallization mechanisms were identified in PM and IM alloys. Different dynamic α precipitation mechanisms were verified and characterized in PM and IM alloys.